Fine Mapping and Candidate Gene Identification for Wax Biosynthesis Locus, BoWax1 in Brassica oleracea L. var. capitata - Liu, Dongming; Dong, Xin; Liu, Zezhou; Tang, Jun; Zhuang, Mu; Zhang, Yangyong; Lv, Honghao; Liu, Yumei; Li, Zhansheng; Fang, Zhiyuan; Yang, Limei (Frontiers in Plant Science, 2018)
Cuticular waxes play important roles in plant protection against various biotic and abiotic environmental stresses. The cuticular wax covering gives normal cabbage a glaucous appearance, but the appearance of waxless mutant is glossy green. Based on the present study, inheritance of the glossy green character of mutant HUAYOU2 follows a simple recessive pattern. Genetic analysis of an F2 population comprising eight hundred and eight recessive individuals derived from HUAYOU2 (P1, maternal parent) and M36 (P2, paternal parent) revealed that a single recessive locus, BoWax1 (Brassica oleracea Wax 1), controls glossy green trait in B. oleracea. This locus was mapped to a region of 158.5 kb on chromosome C01. Based on nucleotide sequence analysis, Bol013612 was identified as the candidate gene for BoWax1. Sequencing results demonstrated that there is a deletion mutation of two nucleotides in the cDNA of Bol013612 of HUAYOU2, which may account for its glossy green trait. These results lay the foundation for functional analysis of BoWax1 and may accelerate research on wax metabolism in cabbage.